Reliability Evaluation of Photovoltaic Modules Fabricated from Treated Solar Cells by Laser‐Enhanced Contact Optimization Process. Issue 5 (5th November 2021) - Krassowski, Eve; Jaeckel, Bengt; Zeller, Ulli; Pander, Matthias; Schenk, Paul; Hofmueller, Eckehard; Hanifi, Hamed
Abstract : According to the International Technology Roadmap for Photovoltaics, passivated emitter and rear solar cells dominate the market in 2021 of up to 80% and are forecast to remain state of the art at least for the next 5 years. Within the production process of solar cells, it is typical to have cells with lower efficiency grades due to variations in manufacturing processes or material defects. Reprocessing such solar cells could save cost due to increased production yield and simultaneously reduced cost for recycling of unusable/unsellable low‐efficiency cells. Herein, the impact of the laser‐enhanced contact optimization (LECO) process on the power output and reliability of solar modules using commercial off‐spec cells of different manufacturers is analyzed. LECO is a downstream process for optimizing metal−semiconductor contacts on finished solar cells. The treatment leads to a significant economic gain due to enhanced cell efficiency (Wp ↑, therefore manufacturing cost per Wp ↓) even of already good solar cells. Herein, the first evaluation of the impact of the LECO process on the cell output power on an industrial scale (>1000 cells) and on module reliability is presented. The results for common short‐term effects like light‐induced degradation and light‐ and elevated temperature‐induced degradation are within expected limits and the durability against, for example, potential‐induced degradation is not changed due to the LECO process. The results further show that cell sorting is crucial for a reliable module and to avoid outliers in terms of unexpected degradation and recovery phenomena of individual cells. Abstract : Herein, the impact of the laser‐enhanced contact optimization (LECO) process on the power output of commercial off‐spec solar cells of different manufacturers is analyzed. The reliability of solar modules comprising the over 1000 LECO‐treated and ‐untreated cells is investigated. LECO is a downstream process for optimizing metal−semiconductor contacts on finished solar cells.